ANALISIS DAN DESAIN WEBSITE E-GOVERNMENT BIDANG PENELITIAN PENGEMBANGAN DAN STATISTIK BAPPEDA KABUPATEN KATINGAN (Universitas Palangka Raya, 2017)
Government agency uses the E-Government technology to facilitate it’s function and to servethe citizen. Research, Development and Statistic Division of BAPPEDA Katingan is the coordinatingunit that perform data collection, analysis, research and report the result of the district developmenton Katingan regency. Research, Development and Statistic Division of BAPPEDA Katingancoordinates the Katingan government unit to collect the development result data. The mechanism tocollect and process data spend a lot of cost and resource, therefore Research, Development andStatistic Division of BAPPEDA Katingan needs information technology such as E-Government tofacilitate it’s tasks.This study aims to analyze and design the Government to Government (G2G) model forResearch, Development and Statistic Division of BAPPEDA Katingan E-Government system, that canbe used as a blue print to develop the E-Government system. The methodology in this study usesseveral phases such as planning and analysis phase, and design phase which is adopted from thestages of software development method waterfall.The results of this study are Blueprint of E-Government System. The blueprint could be thebasis to develop E-Government Systems for Research, Development and Statistic Division ofBAPPEDA Katingan.